PENGARUH PEMBELAJARAN QUANTUM BERBANTUAN PERMAINAN CCTP DAN MIND MAPPING GAME TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA - Purnamasari, Latipah; Aeni, Ani Nur; Sujana, Atep (Jurnal Pena Ilmiah, 2019)
Environmental problems continue to grow. If it is not immediately resolved, the sustainability of the earth will be threatened. Therefore humans must have the ability to think creatively to overcome these environmental problems. The creative thinking must be developed from the age of elementary school especially through science learning. So a quasi-experimental study was conducted for determine the effect of quantum learning assisted by CCTP games and mind mapping games for creative thinking and to find out which is better between the two games in increasing creative thinking. The research sample was VA and VC grade students at Tegalkalong Elementary School located in North Sumedang District. The instruments used are creative thinking test questions and supported by several qualitative data. After learning as many as 3 meetings, the conclusion is obtained that: (1) Quantum learning with the help of these two games can improve the ability to creative thinking. The increase in creative thinking skills of students treated by using quantum learning helfed game of CCTP was no better than students who were treated using quantum learning helfed by mind mapping games significantly (Î¼1 = Î¼2), meaning that both games were not better with each other.